The Relationship between Parenting Patterns and Student Learning Outcomes at SDN 020 North Samarinda: Hubungan Pola Asuh Orang Tua Dengan Hasil Belajar Siswa Sekolah Dasar Negeri 020 Samarinda Utara - Nur Agus Salim; Afdal; Maria Goretti Woga Ngole (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
The purpose of this study was to find out about the relationship between parents’ parenting style and students’ learning outcomes. In specific, this study aimed to determine the relationship between parents’ parenting and students' learning outcomes from Sekolah Dasar Negeri 020 North Samarinda in academic year of 2017/2018. This study used a research method with descriptive quantitative approach, using associative correlational types. The researcher used probability sampling technique with proportionate stratified random sampling type. Data analysis in this study uses quantitative descriptive analysis. Based on the results of research conducted at the Sekolah Dasar Negeri 020 North Samarinda, researcher concluded that the calculation of correlation analysis between parents’ parenting style variables (X) with learning outcomes (Y) resulted in a significance value of 0.000 <0.05, with a comparison of t count value of 0.786 was greater than the value of t table. Thus H0 is rejected, means there was a relationship between parents’ parenting style and students’ learning outcomes. Therefore, the better the parenting style applied by parents to children, the higher the outcomes tend to be. In contrast, the worse the parenting applied by parents, the lower the outcomes tend to be. Parenting style acted as a supporting component in improving student learning outcomes was clearly related